Empirical Investigation of the Impact of Energy intensity and Financial Institutions Efficiency on Environmental Degradation in Pakistan - Azra, Azra; Munir, Shahid; Abbas, Khurram; Khalid, Muhammad Hasnain; Ul Haq, Ihtisham (International Journal of Energy Economics and Policy, 2023)
Pakistan’s is relentlessly affected by climate change and is looking for foreign assistant to deal with climate change challenges. Also, Pakistan is trying to tackle with climate change domestically. Environmental degradation consequently leads to climate change domestically as well as globally. Environmental degradation is extensively studied in empirical literature. Efficient use of resources only can ensure to lessen environmental degradation and its effects in terms of climate change. Henceforth, the current empirical study is analyzing the impact of energy intensity and financial institutions efficiency on environmental degradation in Pakistan. The energy intensity is considered as a factor of environmental degradation as it is one of the proxy for energy efficiency. Moreover, for overall economic activities impact on environmental degradation, this study considered GDP as a control variable. The time series techniques such as unit root and bounds cointegration techniques are applied for non-stationarity, cointegration and results estimates. The result of this study documented that energy intensity, financial institutions efficiency and GDP are factors of environmental degradation and energy intensity and GDP are aggravating environmental degradation whereas financial institutions efficiency has abstained it in Pakistan.